PENERAPAN SISTEM E-FILLING, KESADARAN PERPAJAKAN, DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Cindy Natalia; Ernie Riswandari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to test the influence of E-Filling implementation, tax awareness, and tax sanctions on the compliance of private taxpayers. The population of this research is a private taxpayer who lives in dki Jakarta area who has an NPWP and has used E-Filling. Data in the form of questionnaires disseminated through Google Form and obtained samples used by as many as 100 respondents and processed with Smart PLS 3. The results showed the application of E-Filling system and tax awareness had an effect on the compliance of private taxpayers. While tax sanctions have no effect on the compliance of private taxpayers.